Property optimization of Er/Yb-codoped LiNbO3 crystals for LNOI lasers and amplifiers - Zhongzheng Zhang; Yuqi Zhang; Zhaojie Wu; Xin Yuan; Shiguo Liu; Hongde Liu; Dahuai Zheng; Yongfa Kong; Jingjun Xu (APL Materials)
Lithium-niobate-on-insulator (LNOI) is regarded as an ideal platform for integrated photonics. As an essential part, active devices based on rare-earth (RE) doped LNOI have made significant progress, with erbium/ytterbium-codoped lithium niobate (Er/Yb-codoped LN) showing great potential. In this paper, a series of Er/Yb-codoped LN crystals were successfully grown by the Czochralski method, featuring a fixed Er3+ concentration with various Yb3+ doping levels and a fixed RE3+ (RE3+ = Er3+ + Yb3+) concentration. The absorption and emission spectra were measured, and the transfer efficiencies along with relative conversion efficiencies were also displayed. It was concluded that the optimal composition of codoped LN is ∼1.0 mol. % Er3+ and 1.0 mol. % Yb3+, which can enhance active devices by providing lower threshold power, reduced transmission loss, higher transfer efficiency, and improved conversion efficiency. These results will advance the development of high performance LNOI lasers and amplifiers.